EXPLORING THE STUDENT TEACHERS’ DIGITAL LITERACY AND TEACHING CREATIVITY AT TADRIS BAHASA INGGRIS, FTK UIN MATARAM - Rahmat, Hery; Jaelani (The Center for Language Development, Mataram State Islamic University., 2024)
Teaching Practice Program (PPL) contributes to the development of professional teachers by educating and training the students in practice at schools. Though, some students still lack confidence and are perplexed when they teach in a real classroom setting. This study aims to find out the student teachers at Tadris Bahasa Inggris (TBI), FTK UIN Mataram Digital Literacy level, their Teaching Creativity, and the correlation between the two variables during the Teaching Practice Program. This research is a quantitative approach that used a descriptive correlational design with two variables namely Digital Literacy Level (X) and Teaching Creativity Index (Y). The population of this research is 122 student teachers of the sixth semester enrolled in the Teaching Practice (PPL) course program with 82 students as sample. The researchers use two-part questionnaires namely Digital Literacy scale suggested by Amin et al. (2021) with 27 items and Dikici & Soh's (2015) Creativity Fostering Teacher Behaviour Index (CFTIndex) with 28 items. The research found that (1) The student teachers’ Digital Literacy is 0.722 or 72.2 % or high Category; (2) The student teachers’ Creativity Teaching is 0.7203 or 72.03 % or high Category; and (3) There is a significant correlation between the Digital Literacy and Teaching Creativity at TBI, FTK, UIN Mataram. It is indicated that rtable > rcount (0.522 > 0.213) so that H0 is rejected and Ha is accepted. As it is compared to the coefficient of the interval from 0.40-0.599, the correlation has a level medium relationship.